Dampak Media tehadap Perilaku Masyarakat - Ilah Holilah (Jurnal Studi Gender dan Anak, 2017)
The article discuss about Mass Media and its influence to the people. Deeply, it also explains about the significant functions of Mass Media. In the opinion, the article states that Mass Media is like double-edged of knife; it has possitive effect, and in the other hand it brings a lot of negative effects. Thus, it must be paid attention carefully by the government, the producers of Mass Media and the people. Therefore, the article would like to highlight, explain and discuss the real meaning, character and effects of Mass Media. In addition, the method here is using some theories which were presented by some scholars of Mass Media, and describing some facts and its interpretation. Surely, it gives the new horizan of thinking about Mass media and the people’s response.